Meta-analysis towards FSHD reveals misregulation of neuromuscular junction, nuclear envelope, and spliceosome - Teresa Schätzl; Vanessa Todorow; Lars Kaiser; Helga Weinschrott; Benedikt Schoser; Hans-Peter Deigner; Peter Meinke; Matthias Kohl (Communications Biology, 2024)
Abstract Facioscapulohumeral muscular dystrophy (FSHD) is one of the most common autosomal dominant muscle disorders, yet no cure or amelioration exists. The clinical presentation is diverse, making it difficult to identify the actual driving pathomechanism among many downstream events. To unravel this complexity, we performed a meta-analysis of 13 original omics datasets (in total 171 FSHD and 129 control samples). Our approach confirmed previous findings about the disease pathology and specified them further. We confirmed increased expression of former proposed DUX4 biomarkers, and furthermore impairment of the respiratory chain. Notably, the meta-analysis provides insights about so far not reported pathways, including misregulation of neuromuscular junction protein encoding genes, downregulation of the spliceosome, and extensive alterations of nuclear envelope protein expression. Finally, we developed a publicly available shiny app to provide a platform for researchers who want to search our analysis for genes of interest in the future.